CIBERIDENTIDADES NOS ANOS FINAIS DO ENSINO FUNDAMENTAL PÚBLICO: RELAÇÕES NOS PROCESSOS DE ENSINO E APRENDIZAGEM - MARIN, ELIANE (2020)
The influence of Digital Information and Communication Technologies (TDIC) in contemporary society constitutes differentiated youth identity constructions, requiring that the public school rethink its models based on rigorous content and knowledge centered on teachers and textbooks. The research aimed to understand and analyze the identity constructions formed in interaction with the virtuality of public elementary school students, contributing to discussions and the direction of contextualized teaching and learning processes. Specifically, we sought to historicize Digital Information and Communication Technologies (TDIC) in the Brazilian public school; understand identity virtualization in cyberspace and at school; apply an extension course for public school students. For the implementation of these objectives the problem was: How are the identities of young students being constructed in the real and digital world and what are their relations with the teaching and learning processes in public schools? Based on a bibliographic survey based on authors such as Bauman (2005; 2012), Hall (1997; 2006), Kenski (2007), Leccardi (2005; 2010), Lévy (1999, 2010; 2011), Palfrey and Gasser (2011) and Valente (1999; 2018) carried out action research, with qualitative analysis. The study became relevant to its scope in educational investigations and relevant to understanding the reason for this work, based on the proper theoretical framework and documentary research. Data collection consists of an extension course approved by the Research Ethics Committee, containing a semi-structured questionnaire and a video recording. The extension course took place in the hybrid mode, with weekly studies, aiming in addition to data collection, to certify the participants. The population was composed of 12 (twelve) students inserted in the Technology Center, which is part of the multiserial sectorial division of public elementary school of the school participating in the research. The hypothesis raised that if the public school understands the real and virtual identity constructions of its young students, appropriating teaching and learning processes that meet the configurations of contemporary society, there will be a reduction in the disinterest and inattention of its students, it was verified and found through this study. The data collected indicated that the identities of the contemporary generation are being constructed not only in the real world, but also in the virtual world. It was concluded that for the students surveyed, school processes are distanced from their daily actions with regard to the use of digital technologies, however, their skills are restricted to social networks and online games. Therefore, it is considered that the students showed in their contributions, differences in the ways they construct their identities today, reporting their dissatisfaction with the educational environment and aiming for changes in the teaching and learning processes.